Dawn of the Belle Epoque: The Paris of Monet, Zola, Bernhardt, Eiffel, Debussy, Clemenceau, and Their Friends - McAuliffe, Mary (Rowman & Littlefield Publishers, 2011)
A humiliating military defeat by Bismarck's Germany, a brutal siege, and a bloody uprising—Paris in 1871 was a shambles, and the question loomed, "Could this extraordinary city even survive?" With the addition of an evocative new preface, Mary McAuliffe takes the reader back to these perilous years following the abrupt collapse of the Second Empire and France's uncertain venture into the Third Republic. By 1900, Paris had recovered and the Belle Epoque was in full flower, but the decades between were difficult, marked by struggles between republicans and monarchists, the Republic and the Church, and an ongoing economic malaise, darkened by a rising tide of virulent anti-Semitism. Yet these same years also witnessed an extraordinary blossoming in art, literature, poetry, and music, with the Parisian cultural scene dramatically upended by revolutionaries such as Monet, Zola, Rodin, and Debussy, even while Gustave Eiffel was challenging architectural tradition with his iconic tower. Through the eyes of these pioneers and others, including Sarah Bernhardt, Georges Clemenceau, Marie Curie, and César Ritz, we witness their struggles with the forces of tradition during the final years of a century hurtling towards its close. Through rich illustrations and vivid narrative, McAuliffe brings this vibrant and seminal era to life.